Perancangan Aplikasi Perekrutan Karyawan Berbasis Web Menggunakan Platform Pega - Hindriyanto Dwi Purnomo; Trivena Andriani (AITI, 2020)
Quality of human resources currently needed at a company, therefore the company needs to select candidates through recruitment such as at PT. Asuransi Sinar Mas. The application needed to simplify recruitment then was created a Job Fair application web-based to get information about potential candidates. To design this application used the Prototype model so the application is according to user requirement and using the Pega platform because Pega is more effective in terms of time and can translate business process management to an application according to user requirements. With this application, the company can save paper cost and help the recruitment process from various areas because can be accessed online.